Combination Therapies: Cell Membrane Camouflaged Hydrophobic Drug Nanoflake Sandwiched with Photosensitizer for Orchestration of Chemo‐Photothermal Combination Therapy (Small 20/2019). Issue 20 (17th May 2019) - Zhang, Lijun; Zhang, Xiao; Lu, Guihong; Li, Feng; Bao, Weier; Song, Cui; Wei, Wei; Ma, Guanghui
Abstract : In article number1805544, Wei Wei, Guanghui Ma, and co‐workers develop a nanocrystal‐based delivery system for safe and high‐performance chemo‐photothermal combination therapy. As the core, flake shaped hydrophobic drug nanocrystals are camouflaged with cancer cell membranes for homotypic targeting capacity at tumor sites. Meanwhile, a photosensitizer sandwiched between the nanocrystal and membrane not only converts infrared light to heat for photothermal treatment but also improves the dissolution of hydrophobic drugs for chemotherapy.